The Effect of Audible Joint Manipulation Sounds in the Upper Cervical Spine on Brain Wave and Autonomic Nervous System Activity - Dalton Whitman; Rob Sillevis; Matthew Frommelt (Life)
Background: High-velocity, low-amplitude (HVLA) manipulation is a common manual therapy technique used for treating pain and musculoskeletal dysfunction. An audible manipulation sound is commonly experienced by patients who undergo HVLA manipulation; however, there is little known about the effects and clinical relevance of the audible manipulation sound on cortical output and the autonomic nervous system. This study aimed to identify the immediate impact of the audible manipulation sound on brainwave activity and pupil diameter in asymptomatic subjects following an HVLA cervical manipulation. Methods: 40 subjects completed this quasi-experimental repeated measure study design. Subjects were connected to electroencephalography and pupillometry simultaneously, and an HVLA cervical distraction manipulation was performed. The testing environment was controlled to optimize brainwave and pupillometry data acquisition. Pre-manipulation, immediately after manipulation, and post-manipulation data were collected. The presence of an audible manipulation sound was noted. Results: Twenty subjects experienced an audible manipulation sound. Brainwave activity changes were significant (p < 0.05) in both the audible manipulation sound and non-manipulation sound groups. Pupil diameter changes (p < 0.05) occurred in both eyes of the non-manipulation sound group and in the left eye of the audible-manipulation sound group. Brainwave activity patterns were similar in both groups. Conclusions: The presence of an audible manipulation sound is not required to produce central nervous system changes following an HVLA cervical manipulation; however, the audible manipulation sound does prolong the effects of brainwave activity, indicating a prolonged relaxation effect.